2009
DOI: 10.1345/aph.1m153
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Acute Necrotizing Pancreatitis Revisited

Abstract: Use of antibiotic prophylaxis for patients with necrotizing pancreatitis is not indicated, based on 2 blinded trials. Instead, on-demand use of antibiotics appears to be appropriate. Given progress in intensive care and the high crossover rate in studies, the need for antibiotic prophylaxis may continue to be debated for decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The authors further reasoned that there might have been an apparent publication bias in the period before 2000 but that certain patients with severe pancreatitis could still benefit from antibiotic prophylaxis. In line with this meta-analysis, nearly all new but also some older reviews and meta-analyses [ 10 , 12 , 17 , 19 , 20 , 21 , 23 , 25 , 29 , 30 , 39 , 40 ] conclude that a general recommendation for prophylactic antibiotics cannot be given. Most of these authors also see a need for better trials since some subgroups might benefit from antibiotics.…”
Section: Recommendations For/against Prophylactic Antibiosismentioning
confidence: 52%
See 1 more Smart Citation
“…The authors further reasoned that there might have been an apparent publication bias in the period before 2000 but that certain patients with severe pancreatitis could still benefit from antibiotic prophylaxis. In line with this meta-analysis, nearly all new but also some older reviews and meta-analyses [ 10 , 12 , 17 , 19 , 20 , 21 , 23 , 25 , 29 , 30 , 39 , 40 ] conclude that a general recommendation for prophylactic antibiotics cannot be given. Most of these authors also see a need for better trials since some subgroups might benefit from antibiotics.…”
Section: Recommendations For/against Prophylactic Antibiosismentioning
confidence: 52%
“…However, the data for the outcome of the patients receiving prophylactic antibiosis are conflicting. In this review, we will summarize meta-analyses and reviews on this issue [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] (please also refer to table 1 for a short summary of the included meta-analyses) and will not discuss the original data in detail.…”
Section: Recommendations For/against Prophylactic Antibiosismentioning
confidence: 99%
“…They should be initiated "on demand" (Table 7) and kept no more than 14 days without microbiological demonstration of infection. When comparing prophylaxis and on demand use of ciprofloxacin and metronidazole, Iganatavicius et al concluded that the use of prophylactic antibiotics does not affect mortality rate, but may decrease the need for interventional and surgical management and lower the number of reoperations, [67] while other authors only recommend on demand use of antibiotics [68].…”
Section: Antibiotic Selection In Infected Acute Pancreatitismentioning
confidence: 99%